Defense Spending Cutbacks and Real Interest Rates in the Neoclassical One-Sector and Two-Sector Models - HOON, Hian Teck (Institutional Knowledge at Singapore Management University, 1992)
This paper uses the neoclassical one-sector and two-sector models to examine the behavior of real interest rates in response to cutbacks on defense spending on capital goods and army personnel. It is demonstrated that while a permanent decline in defense spending on capital goods and military personnel leaves the term structure unaffected in the one-sector model, the two-sector model predicts that the short and medium term real interest rates rise to give a downward-sloping yield curve when the capital goods producing sector is relatively labor-intensive.